Acute isolated medial rectus palsy due to infarction as a result of hypercoagulable state: A case report and literature review - Morya, Arvind K (Indian J Ophthalmol, 2019)
Isolated medial rectus palsy in an otherwise healthy individual is a very rare entity. However, this may point towards underlying systemic pathology. This is a case report of an otherwise healthy young adult male who presented with sudden onset non-progressive blurring of vision in right eye. A series of investigations were performed and the patient was diagnosed to have a rheumatological disorder. Isolated muscle palsies in young patient may be masking a systemic disorder and needs to be evaluated thoroughly.